Factors Affecting University Lecturers’ Adoption of Learning Management System (LMS) in Kurdistan Region of Iraq: A Conceptual Framework - T. Sulaiman, Twana; Bali Mahomed, Anuar Shah; Hassan, Mazlan; Rahman, Azmawani Abd (International Journal of Psychosocial Rehabilitation, 2019)
Purpose of the study: This paper presents a conceptual framework underlying research on factors affecting LMS adoption in the Kurdistan Region universities. Although LMS has been widely adopted in universities worldwide, unfortunately, the adoption is still low in the Kurdistan Region universities. Methodology: This paper reviewed relevant literature related to the subject to determine the most significant factors influencing the LMS adoption. More specifically, four factors (organizational, social, individual, andtechnological) were) selected that might be valid for the study context. This study usedthe Technologyy Accepting Model as the primary theory with the combination of the IS Success Model. Main Findings: This conceptual paper provides insightsintof variables related to factors affecting LMS adoption. The mainfindingsg of the study show that organizational factors (facilitating condition, top management support, and top management policy), socialfactorsr (only subjective norm), individual factors (resistance to change andself-efficiency),) and technological factors (service quality and system quality) might havea significantt link withthe preservatione of use,the preservatione ofusefulness,s andthe actuall use ofa learningg management system. Another finding of this study predicted that the actual use of LMS might significantly affect the net benefit (improving lecturers’ and universities’ performance). Applications of this study: This study proposed a conceptual research framework expected to guide KRI university leaders in understanding the most significant factors that must be addressed to adopt LMS among lecturers. Furthermore, understanding those factors might be useful for decisionmakers in the Ministry of Higher Education in KRI to achievethe Ministry’ss pedagogical strategy, modifying from lecturer-centered to student-centered pedagogy. Novelty/Originality of this study: No studyhas beens done before on the lecturer’s influenceonn LMS adoption in higher education in the Kurdistan Region of Iraq.